2004
DOI: 10.5089/9781451875775.001
|View full text |Cite
|
Sign up to set email alerts
|

Local Financial Development and the Aid-Growth Relationship

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
(24 reference statements)
3
18
0
Order By: Relevance
“…Consistent with our hypothesis, we find a negative coefficient of the interactive term suggesting that countries with well-developed financial sectors are associated with lower volatility. This finding is somewhat akin to Nkusu and Sayek (2004). A plausible explanation from this study may be that, because aid provides more resources to governments of the recipient countries reduces their appetite to compete with the private sector for credit from the domestic financial sector thereby freeing credit to the private sector.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…Consistent with our hypothesis, we find a negative coefficient of the interactive term suggesting that countries with well-developed financial sectors are associated with lower volatility. This finding is somewhat akin to Nkusu and Sayek (2004). A plausible explanation from this study may be that, because aid provides more resources to governments of the recipient countries reduces their appetite to compete with the private sector for credit from the domestic financial sector thereby freeing credit to the private sector.…”
Section: Resultsmentioning
confidence: 62%
“…Using a sample of 39 developing between 1975 and 2000, Duc (2006) found a significant negative relationship between aid and economic growth. The other strand of empirical studies (Hansen and Tarp 20001;Nkusu and Sayek, 2004;Ekanayake and Chatrna, 2010;De La Croix and Delavallade, 2013;Young and Sheehan, 2014) note the inconclusiveness with respect to the relationship between aid and growth. Ekanayake and Chatrna (2010) found that foreign aid had a mixed impact on economic growth of developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…This is because both utilization and absorptive capacity affect the country's export competitiveness. Nkusu and Sayek (2004) in their "Local financial development and the aid-growth relationship" assessed 86 countries from 1970-1999 broken into 1970-1999 and 1995-1999. The study followed Mankiw, Romer, and Weil (1992) and used weighted least squares (WLS) regression.…”
Section: Competitiveness and Global Financementioning
confidence: 99%
“…The theory is criticised for failing to prescribe governance values and norms which should be followed in order to bring about desired development and urbanisation [56,57]. Notwithstanding these criticisms, the rationale of this theory offers the principles upon which the development and urbanisation model pursued in Kampala, Uganda, is based [58]. As a matter of fact, the official development and urbanisation programme pursued in Kampala under the PEAP umbrella was developed based on the modernisation theory [59].…”
Section: Theoretical Frameworkmentioning
confidence: 99%